Evolution of a dissipative structure as a model of the process in an earthquake focus: analogies in living systems and chemical kinetics - Kostinsky, A. S. (Reports of the National Academy of Sciences of Ukraine, 2014)
The assumption is made that the emergence, evolution, and decay of a dissipative structure similar to hexagonal Benard cells in a media or a substance with nonlinear properties may cause a phenomenon perceived as the earthquake focus. It is asserted that an effective description of the phenomenon is only feasible in terms of axiomatically built mechanics of excitable media, as an option of the classical kinematic focus models “embedded” in the scheme. The thesis is illustrated by the juxtaposition with a variety of autowave processes in biological and chemical systems.